2018
DOI: 10.1016/j.neurobiolaging.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent regulation of excitatory synaptic transmission at hippocampal temporoammonic-CA1 synapses by leptin

Abstract: The hippocampus is a key target for the hormone leptin and leptin regulation of excitatory synaptic transmission at Schaffer-collateral–CA1 synapses during aging are well documented. However, little is known about the age-dependent actions of leptin at the temporoammonic (TA) input to CA1 neurons. Here we show that leptin induces a novel form of N-methyl-D-aspartate receptor–dependent long-term depression (LTD) at adult (12–24 weeks old) TA-CA1 synapses. Leptin-induced LTD requires activation of canonical Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…Recent evidence indicates that the modulatory actions of leptin at excitatory TA-CA1 synapses is also highly dependent on age (McGregor et al, 2018 ; Figure 1 ; Table 1 ). In juvenile tissue, application of leptin leads to TA-CA1 LTP (Luo et al, 2015 ), whereas a persistent depression (LTD) is observed after leptin addition to adult hippocampal slices (McGregor et al, 2018 ). Moreover like SC-CA1 synapses, the leptin-sensitivity of TA-CA1 synapses markedly decreases in aged tissue, as application of leptin fails to induce LTD at aged TA-CA1 synapses (McGregor et al, 2018 ).…”
Section: Leptin and Agingmentioning
confidence: 96%
See 4 more Smart Citations
“…Recent evidence indicates that the modulatory actions of leptin at excitatory TA-CA1 synapses is also highly dependent on age (McGregor et al, 2018 ; Figure 1 ; Table 1 ). In juvenile tissue, application of leptin leads to TA-CA1 LTP (Luo et al, 2015 ), whereas a persistent depression (LTD) is observed after leptin addition to adult hippocampal slices (McGregor et al, 2018 ). Moreover like SC-CA1 synapses, the leptin-sensitivity of TA-CA1 synapses markedly decreases in aged tissue, as application of leptin fails to induce LTD at aged TA-CA1 synapses (McGregor et al, 2018 ).…”
Section: Leptin and Agingmentioning
confidence: 96%
“…More recent studies indicate that application of leptin also influences the magnitude of excitatory synaptic transmission at another synaptic input to CA1 neurons. This input, which arises in the entorhinal cortex (EC), forms part of the temporoammonic (TA) pathway (Luo et al, 2015 ; McGregor et al, 2018 ; Figure 1 ). Indeed, application of leptin to juvenile (11–18) hippocampal slices induces LTP at this synaptic connection (Luo et al, 2015 ), which directly contrasts with the leptin-induced depression of synaptic transmission observed at SC-CA1 synapses at this age (Moult and Harvey, 2011 ).…”
Section: Leptin Regulation Of Hippocampal Synaptic Functionmentioning
confidence: 99%
See 3 more Smart Citations